The 1962 Iowa corn yield test - Hutchcroft, C. D.; Ingledue, R. D.; Higgs, R. L.; Robinson, J. L. (Iowa State University Digital Repository, 1963)
The Iowa Com Yield Test, conducted since 1920, is an aid to Iowa farmers in selecting corn hybrids adapted to their farms. The order of listing the hybrids has been changed from preceding years. Ranking is according to maturity, with the driest hybrid placed first and followed by other hybrids in order of the increasing moisture content of the com at harvest. The reader will need to keep this in mind when using this publication. The presentation of data does not imply approval or endorsement of any of the hybrids tested, by the authors or by the agencies sponsoring or conducting the test. The state was divided into 12 districts, and two test fields were planted in each district as shown on the map (fig. 1). In addition, two maturity fields were planted at Ankeny and Kanawha. Table A lists the name and address of each cooperator on whose land a test field was planted in 1962 and also the planting and harvesting dates for each field for the past 4 years. Field 3B planted at Postville was severely damaged by hail and was not harvested. The data shown for district 3B are for the period 1958 through 1961.